Islam Nusantara, ulemas, and social media: understanding the pros and cons of Islam Nusantara among ulemas of West Sumatera - Benny Ridwan; Iswandi Syahputra; Azhari Akmal Tarigan; Fatahuddin Aziz Siregar (IAIN Salatiga, 2019)
The concept of Islam Nusantara, which is defined as Islam that accommodates the customs and culture of the (Indonesian) Archipelago, has been rejected by the West Sumatera branch of Indonesian Ulema Council (MUI). Meanwhile, other groups in West Sumatera support the Islam Nusantara concept. This article explains the pros and cons of Islam Nusantara among religious leaders in West Sumatera in the context of social media activities. Ulemas rejected Islam Nusantara in West Sumatera based on the perspective that Islam as a religion has reached peak perfection,adding the word Nusantara is, thus, unnecessary. Other religious leaders in West Sumatera have embraced Islam Nusantara based on the view that in terms of customs in Minangkabau, the principle of Adaik Bersandi Syarak, Syarak Bersandi Kitabullah is followed. This is a field study employing the qualitative method of approach. Data were obtained via in-depth interviews with four West Sumatran religious figures (ulemas) and subsequently analyzed in an interpretative and descriptive manner. The findings in this study show that the ulemas’ rejection of Islam Nusantara via Facebook indicates a shift in the definition of ulemas as religious leaders to that of opinion makers. This is a new finding that has never been studied before as it places the pros and cons of Islam Nusantara within the context of virtual culture. Consequently, this study has implications on the definition of ulemas as religious leaders overlapping with their part as opinion makers and opinion leaders in the current era of new media.Gagasan Islam Nusantara sebagai Islam yang mengakomodir adat dan budaya Nusantara ditolak kehadirannya oleh Majelis Ulama Indonesia wilayah Sumatera Barat. Sementara itu terdapat kelompok lain yang mendukung gagasan Islam Nusantara di Sumatera Barat. Artikel ini menjelaskan pro dan kontra di antara pemuka agama tentang Islam Nusantara di Sumatera Barat dalam konteks aktivitas di media sosial. Islam Nusantara di tolak oleh Ulama di Sumatera Barat didasari oleh pandangan umum bahwa Islam sebagai agama telah mencapai sempurna, sehingga tidak diperlukan penambahan kata Nusantara. Sedangkan pemuka agama lainnya menerima Islam Nusantara di Sumatera Barat karena didasari oleh pandangan umum bahwa adat di Minangkabau Sumatera Barat berpegang pada prinsip Adaik Bersandi Syarak, Syarak Bersandi Kitabullah. Data penelitian dikumpulkan melalui wawancara mendalam terhadap empat pemuka agama (ulama) di Sumatera Barat. Temuan penelitian ini menunjukkan bahwa aktivitas ulama yang menolak Islam Nusantara melalui facebook menggambarkan pergeseran makna Ulama dari religius leader ke opinion maker. Namun pergeseran tersebut justru mengokohkan ulama sebagai pemilik otoritas keagamaan. Temuan ini dapat berimplikasi pada terminologi ulama sebagai religius leader pada era media baru akan berhimpitan dengan terminologi opinion maker dan opinion leader sebagai terminologi baru pada era media baru.